English language education in primary schooling in Argentina - Porto, Melina (2016)
This article describes public primary English language education in Argentina. I begin with background information about the country and a brief historical overview of education in general, accompanied by a portrait of primary schooling in particular. This overview involves local, political and economic considerations but also international influences that have played a key role in shaping the direction of language policies in primary education at the provincial and national levels in the country. I describe the national curriculum guidelines (Núcleos de aprendizaje prioritario, NAP) for foreign language education, contextualising them within the national education policies for primary school in force since 2003 and the new National Education Act (Ley Nacional de Educación 26.206). These guidelines and policies adopt an intercultural and plurilingual approach in the teaching of foreign languages, including English, at all levels of education and embrace a social justice conceptualisation of education in all cases. This approach has been materialised in ELT curriculum developments and programs in several of the 24 jurisdictions of the country with different degrees of development. I illustrate with the cases of the provinces of Buenos Aires, La Pampa, Entre Ríos and Chubut using interview data collected in 2015. Program leaders in these provinces describe their local initiatives. The article closes with a brief account of the affordances observed and the challenges ahead.